Benefits of employee involvement in strategic planning - Henttonen, Heidi (My University, 2025)
There is a change in the field of strategic planning due to rapidly changing business environment. Traditional strategic planning is challenging in a volatile business environment where formal control mechanism and hierarchical structures does not work effectively. Flexibility and adaptation are essential responses to changes in the competitive environment. Suggesting that organizations are moving away from traditional hierarchical structures, where strategies are developed solely by the managers and bring into focus actors outside traditional definition of corporate strategy at different levels of an organization. This Master’s thesis examines employee participation in the strategic planning process and decision-making. The thesis aims to answer the question of the potential benefits of employee involvement in strategic planning for both companies and employees. This thesis also examines the factors affecting employee participation. The benefits of participatory strategic planning are highlighted by applying the microfoundations approach, as it identifies the connection between individual activities and the macro level and is therefore essential approach in explaining the effects of strategic planning and their connections. Previous studies have identified a positive link between strategic planning and organizational success, but they prioritize the collective concepts of organizations over individuals and focus mainly on the managerial perspective and top-down decision-making. This thesis also examines the perspective of employees and aims to increase the understanding of effective strategic planning processes. The thesis uses an exploratory sequential approach and is guided by qualitative semi-structured interviews and quantitative descriptive survey analysis. The methodology is based on a case study approach which allows for a deeper examination of the perspectives of managers and employees at different levels of the organization. The interview and survey data have been analyzed with thematic analysis to create a comprehensive understanding of the participants' perspectives. The results of the thesis identify factors that affect employees' opportunities to participate in strategy work. The most significant factors identified are strategic understanding, strategy communication, and organizational culture. In addition, the study identifies many different benefits for both the company and the employees from the employee involvement in the strategy work. The symbiotic relationship of benefits is found to play a key role. The results of this study highlight the importance of employee participation and provide a new perspective on strategic planning by proposing a wider use of participatory strategic planning processes.

Strateginen suunnittelu on murroksessa toimintaympäristön nopeiden muutosten vuoksi. Perinteinen strateginen suunnittelu on haastavaa epävakaassa ympäristössä, jossa muodolliset ohjauskeinot ja hierarkkiset rakenteet eivät toimi hyvin. Joustavuus ja sopeutuminen ovat olennaisia vastauksia kilpailuympäristön muutoksiin. Tämä viittaa siihen, että organisaatiot ovat siirtymässä pois perinteisistä hierarkkisista rakenteista, jossa strategioita kehitetään pelkästään ylimmän johdon panokseen perustuen, ja tuo keskiöön toimijoita perinteisen yritysstrategian määritelmän ulkopuolelta organisaation eri tasoilta. Tässä pro gradu -tutkielmassa tutkitaan työntekijöiden osallistumista strategiseen suunnitteluprosessiin ja päätöksentekoon. Tutkielmassa pyritään vastaamaan kysymykseen työntekijöiden osallistumisen mahdollisista hyödyistä strategiseen suunnitteluun sekä yrityksille että työntekijöille. Tutkielmassa tarkastellaan myös työntekijöiden osallistumiseen vaikuttavia tekijöitä. Osallistavien strategioiden hyötyjä korostetaan soveltamalla microfoundations lähestymistapaa, sillä se tunnistaa yksittäisten toimintojen yhteyden makrotasolle ja on siten olennainen lähestymistapa strategisen suunnittelun vaikutusten ja niiden yhteyksien selittämisessä. Aiemmat tutkimukset ovat tunnistaneet positiivisen yhteyden strategisen suunnittelun ja organisaation menestyksen välillä, mutta niissä priorisoidaan organisaatioiden kollektiivisia käsitteitä yksilöiden sijaan, ja ne keskittyvät pääasiassa johtajien näkökulmaan ja ylhäältä alaspäin tapahtuvaan päätöksentekoon. Tässä tutkielmassa tarkastellaan myös työntekijöiden näkökulmaa ja pyritään lisäämään ymmärrystä tehokkaista strategisen suunnittelun prosesseista. Tutkielmassa käytetään tutkivaa peräkkäistä lähestymistapaa ja ohjaavana menetelmänä kvalitatiivisiin puolistrukturoituihin haastatteluihin ja kvantitatiiviseen kuvailevaan kyselyyn perustuvaa analyysia. Metodologiana on tapaustutkimus, joka mahdollistaa johtajien ja työntekijöiden näkökulmien syvemmän tarkastelun organisaation eri tasoilla. Haastattelu- ja kyselyaineisto on analysoitu temaattisella analyysilla osallistujien näkökulmien syvemmän ymmärtämisen luomiseksi. Tutkielman tuloksissa tunnistetaan tekijöitä, jotka vaikuttavat työntekijöiden mahdollisuuksiin osallistua strategiatyöhön. Merkittävimmät tunnistetut tekijät ovat strateginen ymmärrys, strategiaviestintä ja organisaatiokulttuuri. Lisäksi tutkielmassa tunnistetaan monia erilaisia etuja sekä yritykselle että työntekijöille henkilöstön osallistumisesta strategityöhön. Hyötyjen symbioottisella suhteella havaitaan olevan keskeinen rooli. Tämän tutkimuksen tulokset korostavat työntekijöiden osallistumisen tärkeyttä ja tarjoavat uuden näkökulman strategiseen suunnitteluun ehdottamalla osallistavien strategioiden laajempaa hyödyntämistä.
Keywords: strategic planning; employees; corporate strategies; participation; benefits; decision making; strategy work; involvement (participation); fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development